KOLABORASI MIS MAARIF NGADIKERSO PADA MASYARAKAT NGADIKERSO DALAM PROSES PENDIDIKAN - Ali, Fachry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the collaboration between MIS Maarif Ngadikerso, an elementary Islamic school in Ngadikerso village, and the local community. Using a qualitative approach with case studies through interviews, observations, and documentation, the research finds that this collaboration enhances students' learning motivation, social skills, and enrichment of learning materials. The main challenges include limited resources and low community involvement, addressed through effective communication and partnerships with government and non-government organizations. This collaboration is crucial for improving educational quality and local relevance. Keywords: collaboration, community, education, islamic school